2012
DOI: 10.2486/indhealth.ms1383
|View full text |Cite
|
Sign up to set email alerts
|

Frequency Weighting for Vibration-induced White Finger Compatible with Exposure-response Models

Abstract: An analysis has been performed to derive a frequency weighting for the development of vibration-induced white finger (VWF). It employs a model to compare health risks for pairs of population groups that are selected to have similar health outcomes from operating power tools or machines with markedly different acceleration spectra (rock drills, chain saws, pavement breakers and motorcycles). The model defines the Relative Risk, RR f(trial) , which is constructed from the ratio of daily exposures and includes a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 33 publications
1
20
0
1
Order By: Relevance
“…Workplace studies, like those reported here by Bovenzi 7) , Brammer and Pitts 8) , and Pitts et al 9) , depend on reliable and consistent diagnosis of hand-arm vibration injuries and reliable and consistent evaluation of workplace exposures. Fundamentally these both are dependent on accurate reporting by individual workers, as well as accurate measurement of power tool and machine vibration.…”
Section: Uncertainty and Inconsistency Of Diagnosis And Measurementsupporting
confidence: 58%
“…Workplace studies, like those reported here by Bovenzi 7) , Brammer and Pitts 8) , and Pitts et al 9) , depend on reliable and consistent diagnosis of hand-arm vibration injuries and reliable and consistent evaluation of workplace exposures. Fundamentally these both are dependent on accurate reporting by individual workers, as well as accurate measurement of power tool and machine vibration.…”
Section: Uncertainty and Inconsistency Of Diagnosis And Measurementsupporting
confidence: 58%
“…Epidemiology studies have generally found only weak agreement between the occurrence of VWF and predictions based on the ISO 5349-1:2001 model (e.g. Griffin et al 2003;Bovenzi 2010Bovenzi , 2012Brammer and Pitts 2012). Both overestimation and underestimation of the occurrence of VWF have been reported (Futatsuka et al 1984;Gemne et al 1993;Griffin 1994), leading to doubts as to whether the frequency weighting for hand-transmitted vibration is appropriate for the assessment of vibration-induced vascular effects (Griffin 2012).…”
Section: Control the Risk Of Vibration Exposurementioning
confidence: 99%
“…The fixed surround around the vibrating contactor in the present study was designed to (Griffin, 2012). Epidemiological studies suggest that frequency weighting W h may not be optimum for predicting the incidence of vibration-induced white finger from occupational exposures to hand-transmitted vibration, with the weighting underestimating the severity of high frequency vibration relative to the severity to low frequency vibration (Griffin et al, 2003, Bovenzi, 2010, Brammer and Pitts, 2012). …”
Section: Finger Blood Flow After Vibration Exposurementioning
confidence: 99%